Electroconvulsive shock increases tachykinin NK(1) receptors, but not the encoding mRNA, in rat cortex. - Burnet, P; Miller, R; Lewis, L; Pei, Q; Sharp, T; Harrison, P (2001)
Recent studies have suggested that the substance P (tachykinin NK(1)) receptor may be a pharmacological target for the treatment of mood disorders. Here, the effects of electroconvulsive shock on tachykinin NK(1) receptor gene expression in the rat brain was investigated. Rats received either a single electroconvulsive shock or five shocks on alternate days. Quantitative autoradiography with [(125)I]Bolton Hunter-substance P, and in situ hybridisation histochemistry, were used to measure tachykinin NK(1) receptor-binding site densities and mRNA abundance, respectively. Densities of tachykinin NK(1) receptor-binding sites were significantly increased in the cerebral cortex following repeated electroconvulsive shock compared to sham treated animals. Densities remained unchanged in the hippocampus, striatum and amygdala. Neither single nor repeated electroconvulsive shock altered tachykinin NK(1) receptor mRNA in the brain regions examined. Hence, repeated electroconvulsive shock increases tachykinin NK(1) receptors in the rat brain in a regionally specific way. Upregulation of receptor-binding sites without a change in mRNA indicates that translational or post-translational mechanisms underlie this process.